PENINGKATAN PEMAHAMAN PEMASARAN DIGITAL SEDERHANA PADA KELOMPOK WANITA TANI (KWT) DESA DUSUN BARU II KECAMATAN KARANG TINGGI KABUPATEN BENGKULU TENGAH - Redy Badrudin; Reswita, Reswita (JURNAL PENGABDIAN MANDIRI, 2025)
The goal of this type of program is to improve cognitive (understanding) capabilities in order to raise attitude levels and develop basic digital marketing abilities through WhatsApp (WA) of Women Farmer Grroup . Videos, conversations, and online instruction (oral slides) are the techniques employed. Pretest and posttest data that "increased" cognitive or basic digital marketing understanding, as well as the comprehension of 94.29% of 35 participants, demonstrate the activity’s effectiveness. Nearly every member takes part.Understanding increased from Less Understanding to Majority Understanding as a result of the activity’s execution. the activity’s success. The implementation advice is really successful